2019
DOI: 10.1016/j.ijscr.2019.03.061
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal ischemia due to methamphetamine use: A case report

Abstract: Highlights Methamphetamine is associated with non-occlusive intestinal ischemia. Splanchnic vasocontriction of mesenteric and colonic vessels is the most likely cause of methamphetamine-induced intestinal ischemia. Surgeons should have a high index of suspicion for intestinal ischemia in methamphetamine users who present with acute abdominal pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Cases of people who chronically use METH and suffer from gastrointestinal diseases, such as nonocclusive mesenteric ischemia 48 and intestinal ischemia 49 , may help explain these changes in the gut microbiota composition. Our results showed that several gut microorganisms, including Fusobacteria, Fusobacteriia, Fusobacteriales and Fusobacteriaceae , were negatively correlated with the duration of METH use.…”
Section: Discussionmentioning
confidence: 99%
“…Cases of people who chronically use METH and suffer from gastrointestinal diseases, such as nonocclusive mesenteric ischemia 48 and intestinal ischemia 49 , may help explain these changes in the gut microbiota composition. Our results showed that several gut microorganisms, including Fusobacteria, Fusobacteriia, Fusobacteriales and Fusobacteriaceae , were negatively correlated with the duration of METH use.…”
Section: Discussionmentioning
confidence: 99%
“…Methamphetamine may lead to cardiovascular complications through catecholamine toxicity, due to its high-affinity interactions with binding sites on the dopamine, norepinephrine, and serotonin receptors (47). Several clinical and postmortem studies have reported an association between amphetamine use and cardiovascular disease (4)(5)(6)48,49), and several clinical case reports (9,10,26,50,51) have reported that methamphetamine use may be a cause of nonobstructive i n t e s t i n a l i s c h e m i a . O n e s t u d y r e p o r t e d t h a t methamphetamine use may be associated with significant microvascular compromise, which increases the risk of mesenteric ischemia (50); however, the mechanisms of these pathological responses in the intestinal tissue of methamphetamine users are still largely unknown (4).…”
Section: Methamphetamine Use Impairs Mesenteric Vasodilator Functionmentioning
confidence: 99%
“…However, abdominal complications due to methamphetamine use are uncommon and often ignored by clinicians (9); consequently, the resulting gastrointestinal pathology has rarely been reported. Although some cases of life-threatening abdominal complications caused by methamphetamine-induced mesenteric ischemia have been described previously (3,9,10), systematically organized domestic studies are lacking. A previous study (11) reported that gut dysbiosis impaired the intestinal barrier and impaired innate immune function in methamphetaminedependent rats, leading to inflammation and infection.…”
Section: Introductionmentioning
confidence: 99%
“…This psychoactive drug is neurotoxic and proven to cause cognitive deficits including a range of adverse impacts on attention, executive functions, information processing, episodic, visual, learning memory, language, and motor skills [ 3 - 5 ]. However, its production and abuse have continued to increase over the years [ 6 , 7 ]. There are well-documented cardiovascular and cerebrovascular pathologies of this drug.…”
Section: Introductionmentioning
confidence: 99%